FROM DAYAH TO HIGHER EDUCATION FOUNDATIONS: THE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS TEUNGKU CHIK PANTE KULU BANDA ACEH (1962-2017) - Anissa Rahmi . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2019)
The study, entitled "From Dayah to Higher Education Foundations: The development of educational Institutions Teungku Chik Pante Kulu Banda Aceh, 1962-2017", raises the question of how the Dayah Teungku Chik Pante Kulu was born, the development of the Teungku Chik Pante Kulu Foundation, andthe changes in status of dayah became a public collage.The method used is historical method with qualitative approach, while data collection technique using libraly research (study of literature) and field research that includes observation, documentation and interview.Based on the research that has been done, obtained the following results: The background of the establishment of the Dayah Teungku Chik Pante Kulu for the improvement of the Darussalam City/Student City development efforts in order to form a large soul, knowledgeable and noble character. In its development the Teungku Chik Pante Kulu Foundation had no progress and there was no development of "failure" because it could not maintain the existence of the dayah at that time. In terms of students experiencing a very drastic decline, facilities and infrastructure are still lacking and not sufficient for the teaching and learning process, and the lecturers owned are also fewer and fewer. This foundation is also hampered in the field of funding because there is no funding assistance from the government and the private sector. The change in dayah became a public university because the people's interest continued to decrease every day, it was difficult to get Teungku Chik and Teungku in Balee and the community wanted to get a degree like other universities.Keywords: Development, Teungku Chik Pante Kulu Foundation